Reliability and validity of the Nepean Beliefs Scale for delusions and overvalued ideas in chronic schizophrenia: analysis of a preliminary pilot study - Ishigaki, Takuma; Shimada, Takeshi; Tanoue, Hiroki; Yoshinaga, Naoki; Nishiguchi, Yuki; Ishikawa, Ryotaro; Hosono, Masahito (Frontiers in Psychiatry, 2023)
Introduction The Nepean Beliefs Scale by Brakoulias et al. is an interview-based multidimensional instrument that measures pathological beliefs in various psychiatric disorders. This study examined the reliability and validity of Nepean Beliefs Scale (NBS) for delusions and overvalued ideas in patients with chronic-phase schizophrenia. Methods: Multiple raters at two healthcare settings examined the beliefs of 28 individuals with schizophrenia using the NBS. Concurrently, PANSS, PDI-21, BCIS, PHQ-9 and GAD-7 were administered. Results The NBS had high reliability and correlation with relevant scales. Discussion The NBS was found to have sufficient reliability and validity for assessing the pathological beliefs of patients with chronic schizophrenia. Although NBS is an easy-to-instruct instrument, it should be noted that appropriate explanations and examples should be added to instructions to obtain reliable responses from patients with chronic schizophrenia.